Pahang Pan Asia Biodiversity Work Camp 2011 - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
KUANTAN 22nd March,2011- Pahang State Government organized a one day brainstorming work camp on the Pahang Pan Asia Biodiversity Center (PanBioPHD.com) at The Zenith Hotel, Kuantan.